ANALISIS ISI FILM AYAT-AYAT CINTA DALAM MEMASYARAKATKAN PENDIDIKAN ISLAM - Isnawijayani, Isnawijayani (Publikasi Penelitian Terapan dan Kebijakan, 2009)
This research aims to know the countent analysis of Ayat-Ayat Cinta film in socializing the Islamic Educations by using descriptive method and qualitative/naturalistic approach. The researher also observes directly in the field and having interview with the audiences. The Film content socializes the Islamic education. It could be seen from the languange applied, situation/place, music, sound effect, actor, and the dress worn. It has strong influence to the people's life. So that is why it could be said as religious film which could be alternative entertain media in socializing Islamic education.